The Improvement of Motorcycle Washing Skills Using Task Analysis Method for Children with Mild Intellectual Disabilities in Phase F at SLB Negeri 1 Harau - Ridwan, Muhammad Adek; Zulmiyetri, Zulmiyetri; Ardisal, Ardisal; Taufan, Johandri; Yuliana, Syari (The Future of Education Journal, 2025)
This study is based on the problems faced by students with mild intellectual disabilities in class X at SLB Negeri 1 Harau, who still experience difficulties in performing the skill of washing motorcycles. The aim of this research is to determine the improvement of motorcycle washing skills using a task analysis approach. This research is experimental, employing the Single Subject Research (SSR) design model A-B. The subject of the study is one student with mild intellectual disabilities in class X. The task analysis technique is used as the independent variable, while motorcycle washing skills serve as the dependent variable. Data were collected through performance tests and analyzed visually using a progress chart. The results of the study show that during the baseline phase (A) over three consecutive sessions, the motorcycle washing skills were at 40%. After receiving intervention using the task analysis technique for seven sessions, the skill percentage gradually increased to 53%, 60%, 73%, 80%, 86%, 93%, and eventually reached 100%. This indicates that the use of task analysis is effective in improving motorcycle washing skills for children with mild intellectual disabilities.